Pathogen Infection and Host-Resistance Interactively Affect Root-Associated Fungal Communities in Watermelon - Xu, Lihui; Nicolaisen, Mogens; Larsen, John; Zeng, Rong; Gao, Shigang; Dai, Fuming (Frontiers in Microbiology, 2020)
Interactions of pathogen infection, host plant resistance and fungal communities are poorly understood. Although the use of resistant watermelon cultivars is an effective control measure of watermelon wilt disease, fungal communities may also have significant effects on the development of the soil-borne pathogen complexes. We characterized the root and rhizosphere fungal communities associated with healthy and diseased watermelons of three different cultivars with different susceptibilities towards wilt disease by paired-end Illumina MiSeq sequencing. Thirty watermelon plants including highly wilt-resistant, moderately resistant, and susceptible cultivars were collected from a greenhouse, half of which showing clear wilt symptoms and the other half with no symptoms. Patterns of watermelon wilt disease and the response of the fungal communities varied among the three cultivars. The amount of the pathogen Fusarium oxysporum f. sp. niveum was higher in diseased root and rhizosphere samples, particularly in the susceptible cultivar, and was significantly positively correlated with the disease index of Fusarium wilt. Plant health had significant effects on root-associated fungal communities, whereas only the highly resistant cultivar had significant effects only on the rhizosphere fungal communities. Co-occurrence networks revealed a higher complexity of fungal communities in the symptom-free roots compared to diseased roots. In addition, networks from roots of the highly resistant plants showing symptoms had a higher complexity compared to the susceptible cultivars. Keystone species were identified for the plants with different symptom severity and the different cultivars in the root and rhizosphere, such as Fusarium oxysporum, Monosporascus cannonballus, and Mortierella alpina. Overall, the most important factor determining fungal communities in the roots was plant symptom severity, whereas in the rhizosphere, plant genotype was the most important factor determining fungal communities.